Interactions involved in heat‐induced gelatin gel containing hsian‐tsao gum, and mechanisms to improve its properties. (13th September 2022) - You, Gang; Niu, Gaigai; Zhou, Xinyi; Fan, Heliang; Liu, Xiaoling
Abstract: Background: Hsian‐tsao gum (HG) has unique gel‐promoting and nutritional properties; however, its use in processed foods is limited to starchy foods, partially due to a lack of knowledge related to its interaction with proteins. This study elucidated the interaction mechanism of heat‐induced gelatin (G) (50 g kg −1 ) gel fortified with HG (0 ~ 20 g kg −1 ) using rheology, Fourier‐transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), large deformation tests, low‐field nuclear magnetic resonance (LF‐NMR), and confocal laser scanning microscopy (CLSM), and scanning electron microscopy (SEM). Results: Heating promoted synergistic interactions between G and more HG molecules with enhanced apparent viscosity and higher storage modulus G′ than loss modulus G″, thus shortening the gel time ( t g ) of G‐HG sols into gels. Fourier‐transform infrared spectroscopy and DSC also confirmed the chemical interactions that occurred, facilitating the formation of β ‐sheet structures of G. The microstructure of G gradually formed separate, coarse strands, and aggregated as HG was added, as observed by CLSM and SEM. This accelerated the gel formation rate and changed the textural properties. Although HG caused a disruptive decrease in the helix structure of G, it was possible to compensate for this by accelerating synergistic interactions, including depletion attractions and Maillard reactions, by heating. Conclusion: Hsian‐tsao gum interacted synergistically with G as a result of heating and this accelerated the gel formation rate and improved the gel properties. Novel complex gels could be designed by blending HG to improve the gel properties of G in the heat processing of the food gel formulation. © 2022 Society of Chemical Industry.